O znaczeniu Świny we wczesnym średniowieczu - Rębkowski, Marian (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2018)
The article contains an analysis of archaeological and historical sources related to the Świna, one of three straits constituting the mouth of the Oder to the Baltic. By referring to the sources, an attempt was made to evaluate the ways of taking advantage of the strait and its significance in the early Middle Ages.